Analisis Fear of Missing Out (FoMO) Labubu terhadap Pembelian Impulsif di Kalangan Masyarakat Indonesia - Vera Maria; Fina Shofia Irpani; Nazwa Alifia Khariza; Vinny Ramadhani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In the digital era, the Fear of Missing Out (FoMO) phenomenon has impacted impulse buying behaviour among Indonesians. This also has a positive impact on businesses, which can benefit greatly from the FoMO effect. With the increasing use of social media, especially on e-commerce platforms, FoMO has become a psychological factor that determines people's impulse purchase decisions. This research examines the phenomenon of Fear of Missing Out (FoMO) by using a qualitative method approach. This research is made through in-depth observation of the Indonesian community. This research can provide new insights for understanding people's behaviour in impulse buying in the digital era.